Resistance behaviours towards mobile commerce applications: A study among mobile users - Hew, Jun Jie (2024)
This chapter first details the research background and problem statement that motivates the conduct of this study. Following these, research questions and objectives are formed accordingly. Afterwards, this study’s significance is discussed from theoretical, practical, and policy perspectives, followed by the scope of study. The relevant details of research background are elaborated in this subsection. The evolution of mobile commerce (m-commerce) is first elaborated, followed by a detailed discussion on m-commerce applications. Moreover, other important concepts associated with this study, namely privacy concerns, technostress, and innovation resistance behaviours are introduced next.